Islamic Law on Gender Based Sexual Violence - Iffatin Nur (Universitas Islam Negeri Jakarta, 2013)
Abstrak: Hukum Islam tentang Kekerasan terhadap Perempuan Berbasis Jender. Dalam pandangan hukum Islam, kekerasan seksual berbasis gender dikenal dengan istilah “al-intihā’ ‘ala ḥurmah al-nisā’ or al-waṭ’ bi al-ikrāh”. Di bidang hukum pidana Islam, ada tiga jenis hukuman terhadap kejahatan, yaitu: qiṣāṣ, ḥudūd, dan ta‘zīr (takzir). Qiṣāṣ adalah hukuman yang setara dengan kejahatan yang dilakukan, termasuk pembunuhan, melukai, atau serangan yang disengaja. Ḥudūd mengacu pada hukuman terhadap kejahatan spesifik sebagaimana terdapat dalam Alquran dan Sunah. Termasuk dalam kategori ini perzinaan, menuduh seseorang melakukan zina, mencuri, ḥirābah, dan tindakan memberontak terhadap Pemerintahan islami dan sah. Sedangkan takzir adalah jenis hukuman terhadap kejahatan lain yang diputuskan oleh hakim Muslim. Kejahatan seksual yang berbasis gender dalam artikel ini dapat digolongkan dalam tiga bentuk yaitu: perzinaan yang dipaksakan, serangan terhadap qiṣāṣ, dan prostitusi yang dipaksakan.Kata Kunci: hukum Islam, kekerasan seksual, genderAbstract: Islamic Law on Gender Based Sexual Violence. In the view of islamic law, gender based sexual violence is known by the term “al-intihā’ ‘ala ḥurmah al-nisā’ or al-waṭ’ bi al-ikrāh”. In the area of Islamic criminal law, there are three types of punishment toward crimes. They are: qiṣāṣ, ḥudūd, and ta‘zīr. Qiṣāṣ is a short punishment equal to the crimes committed including murder, wounding or intentional attacks. Ḥudūd refers to punishment toward some spesific crimes that have been explained by god through revelation. Kind of crimes and their corresponding form of punishment were disceibed in the holy Quran and the prophet Muhammad’s traditions. Including in this kategory is adultery, accusing some one to commit addultery, stealing, ḥirābah, and organising rebellious actions againts an islamically legal and good government. Whereas ta‘zīr is a type of punishment toward other crimes where its forms are left to consideration and decision of Muslim judges. Gender based sexual violence in this article can take three forms of crim which is a forced adultery, an assault in qiṣāṣ, and a forced prostitution.Keywords: Islamic law, sexual violence, gender